Methylation and transcriptomic expression profiles of HUVEC in the oxygen and glucose deprivation model and its clinical implications in AMI patients - Tang, Yuning; Wang, Yongxiang; Wang, Shengxiang; Wang, Runqing; Xu, Jin; Peng, Yu; Ding, Liqiong; Zhao, Jing; Zhou, Gang; Sun, Shougang; Zhang, Zheng (Frontiers in Genetics, 2023)
The obstructed coronary artery undergoes a series of pathological changes due to ischemic-hypoxic shocks during acute myocardial infarction (AMI). However, the altered DNA methylation levels in endothelial cells under these conditions and their implication for the etiopathology of AMI have not been investigated in detail. This study aimed to explore the relationship between DNA methylation and pathologically altered gene expression profile in human umbilical vein endothelial cells (HUVECs) subjected to oxygen-glucose deprivation (OGD), and its clinical implications in AMI patients. The Illumina Infinium MethylationEPIC BeadChip assay was used to explore the genome-wide DNA methylation profile using the Novaseq6000 platform for mRNA sequencing in 3 pairs of HUVEC-OGD and control samples. GO and KEGG pathway enrichment analyses, as well as correlation, causal inference test (CIT), and protein-protein interaction (PPI) identified 22 hub genes that were validated by MethylTarget sequencing as well as qRT-PCR. ELISA was used to detect four target molecules associated with the progression of AMI. A total of 2524 differentially expressed genes (DEGs) and 22148 differentially methylated positions (DMPs) corresponding to 6642 differentially methylated genes (DMGs) were screened (|Δβ|>0.1 and detection p<0.05). After GO, KEGG, correlation, CIT, and PPI analyses, 441 genes were filtered. qRT-PCR confirmed the overexpression of VEGFA, CCL2, TSP-1, SQSTM1, BCL2L11, and TIMP3 genes, and downregulation of MYC, CD44, BDNF, GNAQ, RUNX1, ETS1, NGFR, MME, SEMA6A, GNAI1, IFIT1, and MEIS1. DNA fragments BDNF_1_ (r=0.931, p<0.0001) and SQSTM1_2_NEW (r=0.758, p=0.0043) were positively correlated with the expressions of corresponding genes, and MYC_1_ (r=-0.8245, p=0.001) was negatively correlated. ELISA confirmed TNFSF10 and BDNF were elevated in the peripheral blood of AMI patients (p=0.0284 and p=0.0142, respectively). Combined sequencing from in-vitro cellular assays with clinical samples, aiming to establish the potential causal chain of the causal factor (DNA methylation) -mediator (mRNA)cell outcome (endothelial cell ischemic hypoxic injury)-clinical outcome (AMI), our study identified promising OGD-specific genes, which provided a basis for screening diagnostic and prognostic biomarkers of coronary endothelial cell injury of AMI. Moreover, it furnished the first evidence that during ischemia and hypoxia, the expression of BNDF was regulated by DNA methylation in endothelial cells and elevated in peripheral blood.